The cost-effectiveness of dacomitinib in first-line treatment of advanced/metastatic epidermal growth factor receptor mutation-positive non-small-cell lung cancer (EGFRm NSCLC) in Sweden. (1st January 2021) - Nilsson, Fredrik O. L.; Gal, Peter; Houisse, Ivan; Ivanova, Jasmina I.; Asanin, Sandra T.
Abstract: Aims: Although the benefit of first-line epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) over chemotherapy in EGFR mutation-positive ( EGFR m) non-small-cell lung cancer (NSCLC) has been demonstrated in clinical trials, the optimal treatment sequence remains unclear. The objective of our study was to evaluate the cost-effectiveness of dacomitinib in Sweden vs afatinib and osimertinib in first-line treatment of EGFR m NSCLC. Materials and methods: A partitioned survival model was developed with three health states: progression-free, post-progression, and death. Progression-free and overall survival curves were used to inform movements between states. Clinical data were taken from randomized trials, compared via a network meta-analysis (NMA). Utility data were taken from published studies and costs from national Swedish sources. The model used a 15-year time horizon and a Swedish healthcare payer perspective. Sensitivity and scenario analyses were performed. Results: The base-case analysis showed that dacomitinib accrued a total of 2.10 quality-adjusted life-years (QALYs) at a total cost of Swedish krona (SEK) 874, 615. The incremental cost-effectiveness ratio (ICER) for dacomitinib vs afatinib was SEK 461, 556 per QALY gained. The ICER of osimertinib vs dacomitinib, where the small QALY gains of the former came at a high additional cost, was SEK 11, 444, 709. Deterministic and probabilistic sensitivity analyses confirmed the robustness of these results; changes to drug and medical resource use costs and overall survival had the greatest impact on ICER estimates. Limitations: This model is subject to uncertainty associated with extrapolating long-term treatment effects from shorter trial follow-up periods, although this would also be a limitation when using direct comparison or time-dependent hazard ratios. The NMA was limited by the use of indirect comparison, although sensitivity analyses supported the robustness of our findings. Conclusions: Our model demonstrated that dacomitinib is cost-effective for first-line EGFR m NSCLC treatment in Sweden vs afatinib and osimertinib.